Assessment of the uncertainty budget for an integrated system in clay pigeon shooting discipline - Micheli, M.; Massardi, S.; Morzenti, S.; Pasinetti, S.; Sansoni, G.; Lopomo, N. F.; Lancini, M. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was a part of a wider project to characterize the athletic gesture in the Olympic shooting disciplines, expanding the scientific knowledge in clay pigeon shooting. This project aimed to design and develop an integrated measurement system able to acquire and analyse the shooters` physical parameters. An uncertainty budget was assessed, identifying the main sources of uncertainty for their measurement, being a preparatory step for the validation of a measurement system, which should be able to identify the most relevant parameters affecting the shooting performance.